Influences on COVID-19 Vaccine Hesitancy among Frontline Workers a Case Study of Teachers in Two Diverse Regions in Uganda - Dr. Shira Tendo Namagero (International Journal on Economics, Finance and Sustainable Development, 2021)
COVID-19 is a global pandemic that has disrupted the education system, school calendar and many students have lost a year or two of school. Many teachers in Uganda who are not on government payroll have not had a stable income for over a year. This has created anxiety among both the students and the teachers who are eager to have their schools reopened and are willing to do anything to return to work and school. However, when the teachers were asked to get vaccinated many were reluctant to do so. This paper is a case study of the influences on teachers’ response to mandatory COVID-19 vaccination. Using W.H.O’s immunization survey questions (WHO, 2013), a parallel sampling design was used to compare two regions and the respondents were selected using volunteer/convenience sampling. It was discovered that individual and group influences, contextual influences and vaccine specific issues play a major role in determining community responsiveness to new vaccines.